PERAN ORANG TUA DALAM PEMBELAJARAN - sylvana Talangamin; Heldy Rogahang; Orient Christianty (Peneliti.net, 2021)
The Covid - 19 pandemic that has hit the world, including Indonesia, has brought changes in various spheres of life. Adapting to situations like this is the best choice. The world of education is one of the areas that has undergone significant changes. In general, the wider community thinks that school is a place to learn, in school every student is honed his cognitive abilities, even though other assessments are included such as affective and spiritual assessments. It is in school that cognitive development is experienced by a student, even teacher-student relations are important for a student's self-development towards Indonesia's goal of